2021
DOI: 10.3390/jrfm14030102
|View full text |Cite
|
Sign up to set email alerts
|

Performance Management for Growth: A Framework Based on EVA

Abstract: Some of the constructs in the field of performance management are intuitive or not empirically validated. This study provides a data-driven framework for measuring and improving the performance through synchronized strategies. The ultimate goal was to provide support for increasing business performance. Empirical research materializes in an exploratory case study and a statistical analysis with econometric models. The case study revealed that a company can improve its performance, even in periods of growth, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
8
2
3
Order By: Relevance
“…In this case, ROA seems to affect EVA if the company can more optimally use Current Assets to increase profits. These results contradict the research by Tudose, et al (2021), showing that ROA has a positive and significant effect on EVA. Still, the results of this test are in line with the research by Bhusan & Kumar (2016), which shows that there is no significant effect between financial performance on EVA.…”
Section: There Is An Effect Of Return On Assets (Roa) On Economic Val...contrasting
confidence: 99%
See 2 more Smart Citations
“…In this case, ROA seems to affect EVA if the company can more optimally use Current Assets to increase profits. These results contradict the research by Tudose, et al (2021), showing that ROA has a positive and significant effect on EVA. Still, the results of this test are in line with the research by Bhusan & Kumar (2016), which shows that there is no significant effect between financial performance on EVA.…”
Section: There Is An Effect Of Return On Assets (Roa) On Economic Val...contrasting
confidence: 99%
“…Statistical test results show the value of the level of Indebtedness (LI) in Model 1 has a significance value of 0.0064 < 0.05 and in Model 2 has a significance value of 0.0165 < 0.05, so it can be concluded that the LI has a negative and significant effect on EVA; this means that the more debt the company has, the lower the EVA. These results contradict Tudose et al (2021) and Widasari (2014), which show that the LI and variable debt ratio does not affect EVA.…”
Section: There Is An Effect Of Return On Assets (Roa) On Economic Val...contrasting
confidence: 76%
See 1 more Smart Citation
“…They also showed that EVA and residual income variables are highly correlated and identical to stock returns. Like those authors mentioned above, other researchers [41][42][43][44][45] and authors of more recent studies, e.g., [46][47][48][49][50][51][52][53][54], have also found the EVA useful in financial risk mitigation.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Considering that financial rates are not sufficient to assess performance in today's competitive economy (Safaei Ghadikolaei et al, 2014), the literature has focused on measures based on economic added value. EVA, considered a fourth-generation indicator, has come to the attention of researchers by allowing managers to perform four types of interventions (Kijewska, 2016;Tudose et al, 2021): a) increase the net profit margin (expression of increased efficiency activity); b) increase in sales; c) diminution of the value of the invested capital when it is not fully capitalized; d) optimization of the capital structure.…”
Section: Methodsmentioning
confidence: 99%